2014
DOI: 10.1590/1807-3107bor-2014.vol28.0052
|View full text |Cite
|
Sign up to set email alerts
|

Impact of chemical agents for surface treatments on microhardness and flexural strength of root dentin

Abstract: This study assessed the cross-sectional Knoop microhardness and flexural strength of root dentin exposed to different surface treatments with chemical agents after biomechanical preparation. Root canals from human canines were biomechanically treated and divided into eight groups (n=10) to receive one of the following dentin treatments: I. Deionized water (control); II. 5.25% Sodium hypochlorite (NaOCl); III. NaOCl + 10% Sodium ascorbate (SA); IV. SA; V. 2% Chlorhexidine gel (CHX); VI. 37% Phosphoric acid gel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 27 publications
0
14
0
4
Order By: Relevance
“…It has been suggested that, although chemical substances can reduce tooth hardness, this change in hardness does not interfere with substrate resistance. 30 By contrast, Uzunoglu et al 17 showed that fracture resistance of endodontically treated roots was differently affected by the various EDTA concentrations, followed by irrigation with NaOCl, at different exposure times.…”
Section: Discussionmentioning
confidence: 97%
“…It has been suggested that, although chemical substances can reduce tooth hardness, this change in hardness does not interfere with substrate resistance. 30 By contrast, Uzunoglu et al 17 showed that fracture resistance of endodontically treated roots was differently affected by the various EDTA concentrations, followed by irrigation with NaOCl, at different exposure times.…”
Section: Discussionmentioning
confidence: 97%
“…Different studies have shown that using NaOCl as an irrigating solution signi cantly reduces the microhardness value (31)(32)(33). Most studies used short exposure times of 5-15 min and revealed a reduction in the dentin micro-hardness value compared with irrigating with normal saline(32, 33).…”
Section: Discussionmentioning
confidence: 99%
“…Different studies have shown that using NaOCl as an irrigating solution signi cantly reduces the microhardness value (28)(29)(30). Most studies used short exposure times of 5-15 min and revealed a reduction in the dentin micro-hardness value compared with irrigating with normal saline (29,30). Souza et al reported that an increase in the volume and/or time of exposure to 5.25% NaOCl causes a signi cant reduction in root toughness.…”
Section: Discussionmentioning
confidence: 99%